2013
DOI: 10.1002/anie.201303924
|View full text |Cite
|
Sign up to set email alerts
|

Space‐Confinement‐Induced Synthesis of Pyridinic‐ and Pyrrolic‐Nitrogen‐Doped Graphene for the Catalysis of Oxygen Reduction

Abstract: Forced obedience: Layer‐structured montmorillonite (MMT) was used as a nanoreactor for the generation of planar pyridinic and pyrrolic N sites in nitrogen‐doped graphene (NG; see picture). The selectivity for the formation of planar N sites was inversely proportional to the interspace width (δ) of the MMT and reached a maximum of 90.27 %. The NG catalyst exhibited low electrical resistance, high electrocatalytic activity, and good stability.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

16
458
4

Year Published

2014
2014
2019
2019

Publication Types

Select...
6
3

Relationship

0
9

Authors

Journals

citations
Cited by 662 publications
(478 citation statements)
references
References 41 publications
16
458
4
Order By: Relevance
“…It has been reported in the literature that graphitic N serves as the active site for other catalytic reactions, such as oxygen reduction reaction [54,56] while pyridinic N is active toward OER [33,37]. Depending on the N dopant configurations, electron transfer mechanism in Ndoped carbon nanomaterials can be either p-or n-type [58,59] as has been shown both theoretically and experimentally [33,37,56,60]. Pyridinic N can accept electrons (p-type doping) from adjacent C atoms, facilitating the adsorption of water oxidation intermediates (OH À , OOH À ) as the rate-determining steps for OER in alkaline solution [37].…”
Section: Investigating the Catalytic Active Sites Of The Nmwnt Catalymentioning
confidence: 94%
“…It has been reported in the literature that graphitic N serves as the active site for other catalytic reactions, such as oxygen reduction reaction [54,56] while pyridinic N is active toward OER [33,37]. Depending on the N dopant configurations, electron transfer mechanism in Ndoped carbon nanomaterials can be either p-or n-type [58,59] as has been shown both theoretically and experimentally [33,37,56,60]. Pyridinic N can accept electrons (p-type doping) from adjacent C atoms, facilitating the adsorption of water oxidation intermediates (OH À , OOH À ) as the rate-determining steps for OER in alkaline solution [37].…”
Section: Investigating the Catalytic Active Sites Of The Nmwnt Catalymentioning
confidence: 94%
“…However, it does point to the substantial contributions of pyridinic-and graphitic-N species, presumably by promoting electron transfer and O 2 -adsorption in ORR catalysis. 51,52 Notably, the NGPCs obtained at 1000 C have similar (N1 + N3)/N total ratios (0.87-0.90), but the E onset of NGPC-1000-10 is signicantly higher than those of NGPC-1000-1 and NGPC-1000-5. This can be correlated to the increased portion of graphitic-N as the continuous transformation of pyridinic-N to graphitic-N at prolonged time, suggesting that graphitic-N may contribute more than pyridinic-N to the ORR Table 2 Summary of the electrochemical properties of ORR catalysts activity.…”
Section: Electrocatalytic Performance Of Ngpcs For Orrmentioning
confidence: 96%
“…For example, Ding et al presented a novel strategy for the selective synthesis of pyridinic-and pyrrolic-nitrogen-doped graphene (NG) by the use of layered montmorillonite (MMT) as a quasi-closed flat nanoreactor, as shown in Figure 4. 17 The as-prepared NG exhibits the excellent electronic conductivity, high ORR activity, and good stability in acidic electrolyte. XPS (X-ray photoelectron spectroscopy) and UPS (ultraviolet photoelectron spectroscopy), and concluded that the pyridinic N efficiently changed the valence band structure of graphene, including the raising of density of π states near the Fermi level and the reduction of work function, thus greatly boosting the ORR activity.…”
Section: Nitrogen-doped Graphene (Ng)mentioning
confidence: 99%
“…There are usually several N-containing species in NG, including pyridinic N (~398.7 eV), pyrrolic N (~400.3 eV), quaternary N (~401.2 eV), and N-oxides of pyridinic N (~402.8 eV) as shown in Figure 3. 17 Pyridinic N refers to N atoms at the edges or defects of graphene, which contri ute one π electron to the aromatic π system Pyrrolic atoms with higher binding energy bond to two carbon atoms and contri ute two π electrons to the π system, which are incorporated into five-membered heterocyclic rings. Quaternary N atoms are incorporated into the graphene layer by substituting carbon atoms within the hexagonal ring, which are assigned to N-Q center (graphitic N) and N-Q valley .…”
Section: Nitrogen-doped Graphene (Ng)mentioning
confidence: 99%